1985
DOI: 10.1159/000206222
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Superoxide Dismutase Is Increased in Iron Deficiency Anemia

Abstract: Red blood cells (RBC) from iron-deficient rats were found to generate more malonyldialdehyde after in vitro incubation with H2O2 than RBC from control rats (p < 0.001). The iron-deficient RBC, however, had a higher content of superoxide dismutase (SOD) than control RBC (p < 0.02). This finding suggests an increased formation of SOD compensatory to an increased oxidant stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA. Generally, decreased GSH-Px activity along with normal or increased SOD and CAT activity are the main findings in IDA [10,11]. However, in some studies, normal GSH-Px activity along with decreased SOD and CAT activity or decrease in all of these activities was also reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA. Generally, decreased GSH-Px activity along with normal or increased SOD and CAT activity are the main findings in IDA [10,11]. However, in some studies, normal GSH-Px activity along with decreased SOD and CAT activity or decrease in all of these activities was also reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidant levels and antioxidant enzyme activities such as SOD, GSH-Px and CAT have been evaluated in several studies [8][9][10][11][12][13][14]. Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies of iron deficiency previously have documented either impaired mitochondrial function (18) or increased oxidant stress (9,20), no studies have related the two phenomena. Furthermore, no studies have investigated whether iron deficiency can cause mtDNA damage.…”
mentioning
confidence: 99%
“…Bartal et al (25) found an increased malondialdehyde (MDA) and GSH depletion in red cells exposed to t-butyl hydroperoxide. Other investigators have shown increased MDA and GSH-Px activity (26) and increased superoxide dismutase (27) in red blood cells exposed to hydrogen peroxide. However, it should be pointed out that those researchers used t-butyl hydroperoxide and hydrogen peroxide, which are stronger oxidants than the ion Fe 3+ used in the present study.…”
Section: Resultsmentioning
confidence: 87%